The Cytotoxicity of Eupatorium cannabinum Methanolic Extract in a Human Breast Adenocarcinoma Cell Line (MCF-7) - Shahtaghi, Yasaman; Hamzeloo-Moghadam, Maryam; Mohammadi motamed, Saeid; Esmaeili, Somayeh (International Pharmacy Acta, 2018)
Introduction: Eupatorium cannabinum belonging to Asteraceae family is commonly known as hemp agrimony. E. cannabinum is used to treat headache, hepatitis, diarrhea, diabetes mellitus and hypertension. Considerable researches have been indicated various biological activities of E. cannabinum such as cytotoxic, antioxidant, antimicrobial, anti-inflammatory, immunological and hepatoprotective activities. Since the cytotoxic activity of E. cannabinum on human breast adenocarcinoma cell line (MCF-7) have not been reported, the current study was conducted to evaluate the cytotoxicity of the total extract of E. cannabinum on MCF-7 cells. Methods and Results: MCF-7 cell line was treated with different concentrations (3.125 to 100 μg/mL) of the E. cannabinum total (methanolic) extract. After 48 hrs, the cytotoxic activity was assessed through MTT (3-[4, 5-Dimethylthiazol-2-Yl]-2, 5-diphenyltetrazolium bromide) assay. The methanolic extract demonstrated cytotoxicity against MCF-7 cell line with IC50 (the concentrationthat inhibited cell growth by 50%) value of 69.5 μg/mL. Conclusions: The methanolic extract of E. cannabinum showed considerable cytotoxic activity. Evaluating the apoptosis induction ability of E. cannabinum could be suggested for further studies.